An evaluative survey of the compliance of city and municipal libraries in Laguna with the Minimum Standards for Public Libraries - Ticzon, Ma. Criselle A. (School of Library and Information Studies, University of the Philippines Diliman, 2007)
This study was conducted to evaluate the extent of compliance of the city and municipal libraries in Laguna with the Minimum Standards for Public Libraries formulated by the National Library of the Philippines. The descriptive survey method was used. Data collection was facilitated by personally handing out the structured questionnaires to the librarians. A brief interview with the librarians was also done at some instances in order to complete the survey.